Translation, cross-cultural adaptation and psychometric properties of the Sleep-Related Breathing Disordered−Pediatric Sleep Questionnaire for obese Thai children with obstructive sleep apnea - Khomkrip Longlalerng (2018)
© 2018 Elsevier B.V. Objective: Obstructive sleep apnea (OSA) is a comorbid condition with obesity that can produce deleterious effects on children's health and well-being. Unfortunately, valid instruments for screening OSA in obese Thai children are limited. This study aimed to translate and cross-culturally adapt, from English to Thai, the Sleep-Related Breathing Disordered−Pediatric Sleep Questionnaire (SRBD-PSQ) and to determine its psychometric properties. Methods: The SRBD-PSQ was translated into Thai and cross-culturally adapted. It was administered to 62 parents of obese children and adolescents 7–18 years of age who had polysomnographically confirmed OSA. The psychometric properties including validity, reliability, and diagnostic accuracy were examined. Results: The Thai SRBD-PSQ possessed excellent content validity index for scale (S-CVI = 0.95). An acceptable internal consistency (cronbach's α ≥ 0.7) and good to excellent test−retest reliability (intraclass correlation coefficients [ICCs] = 0.82–0.90) of the Thai SRBD-PSQ and subdomain were observed. There was a significant correlation between the SRBD scale and polysomnography (PSG) indices: apnea−hypopnea index (AHI) and oxygen desaturation index (ODI) (r = 0.35, p < 0.01, and r = 0.27, p < 0.05, respectively). The Thai SRBD-PSQ had an area under the curve of 0.71 (p < 0.05) with a sensitivity of 72% and a specificity of 54%. Conclusion: The Thai SRBD-PSQ is a reliable and valid instrument for use in obese children with OSA. However, the Thai SRBD-PSQ should be used in combination with other investigations.